2013
DOI: 10.4300/jgme-d-12-00175.1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Effectiveness of a Quality Improvement Project to Improve Handoffs to Night Float Residents in an Internal Medicine Residency Program

Abstract: We demonstrated sustained improvements in unreported events and uncertainty caused by poor handoffs. Initial improvements in missed content and copy-and-paste behavior that were not sustained suggest a need for ongoing reinforcement and monitoring of handoff quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Similarly, Graham et al 104 reported improvements in the quality of written accounts of five out of six measures. Yazici et al 103 noted an improvement in five quality markers, but this was sustained to 9 months for only three of them. Gonzalo et al 108 also found limited benefits after 12 months, with no improvement in eight measures of communication and a worsening in communication of results of completed studies/consults.…”
Section: Standardised Handover Toolmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Graham et al 104 reported improvements in the quality of written accounts of five out of six measures. Yazici et al 103 noted an improvement in five quality markers, but this was sustained to 9 months for only three of them. Gonzalo et al 108 also found limited benefits after 12 months, with no improvement in eight measures of communication and a worsening in communication of results of completed studies/consults.…”
Section: Standardised Handover Toolmentioning
confidence: 98%
“…Whether or not this translates into better patient outcomes is not known; despite the majority of studies showing a positive benefit, most of the studies were of poor quality and were small, uncontrolled before-and-after studies. [95][96][97][98][100][101][102][103][104][105][106][107][108][109] Continuing education is the most challenging of the four interventions to assess in terms of the quality and quantity of evidence available. There is some evidence of improved knowledge and self-reported confidence in a range of skills, as well as in process measures, such as frequency of observations, but the evidence for improved patient outcomes is weak.…”
Section: Main Findingsmentioning
confidence: 99%
“…15 Appropriate techniques to identify problems, create solutions, and evaluate long-term effects are central elements for the success and sustainability of any QI intervention, including handoffs. 27 The findings from this study may not necessarily generalize to other handoff implementation venues with different organizational structures and characteristics (eg, large medical centers). This limitation notwithstanding, the findings from this study provide a guiding framework for small and rural hospitals interested in learning from experiences of other similar hospitals that have implemented handoff.…”
Section: Discussionmentioning
confidence: 73%
“…3,4 However, most protocols are developed from brainstorming and consensus instead of from empirical data. Although some evidence suggests that using standardized handoff protocols are better than not using standardized protocols, [5][6][7][8][9] to our knowledge, no studies directly compare 2 different protocols to each other. Considering that protocol use is increasingly common practice, a more pertinent question is which protocol is more effective?…”
mentioning
confidence: 99%